Offshore coverage optimization and application of TD-LTE networks - Junfeng LAN; Chongli NIU; Guohui YU (Dianxin kexue)
With the development of coastal fisheries and marine tourism,the demand for wireless coverage on offshore is becoming more and more urgent.Based on the analysis on the characteristics of the mobile communication business,the difficulties of offshore coverage planning,coverage optimization techniques for the actual application scenarios of coastal areas,a TD-LTE network coverage optimization method which made comprehensive use of the following technologies including special TD-LTE system parameter configuration,optimization of wireless communication link budget,optimization of the base station site planning and coverage enhancement technologies was proposed.The proposed optimization method was practically implemented in the Shangchuan Island and Xiachuan Island.The simulation results and measured data in the project field show that the implementation of TD-LTE network coverage optimization method has obviously improved the network coverage rate and communication service quality.